The Effectiveness of Calcium Supplement as Orally Contrast Media for Gastric Magnetic Resonance Imaging - Zainab Abdulla Mankhi; Khalid Ibrahim Riah; Ahmed Mehmood Abdul-Lettif (مجلة بغداد للعلوم)
The objective of the present work aims to find an alternative oral contrast agent that could be used in magnetic resonance imaging (MRI) of the gastrointestinal system and satisfy the following criteria: it should be safe, it has no or few side effects, it is inexpensive, and it produces the highest imaging quality. The method: We prepared samples (solutions) as oral contrast agents by separately dissolving calcium and magnesium supplements (taken daily dose) in varied quantities of distilled water. In order to identify the sample with the lowest concentration and best quantitative image, the samples were examined in MRI by phantoms. After that, the best sample was tested by ten healthy individuals. The image result is measured by the signal value to calculate signal to-noise-ratio (SNR), relative signal to noise ratios (RSN) and contrast (C) and then a different test is performed. There were significant variations in stomach signal values between pre and post contrast (p-value 0,05). The results: The results showed that the magnesium supplement has essentially no effect on the water signal intensity in T1-weighted and T2-weighted, whereas the calcium supplement enhances the signal intensity of the water in T2-weighted. The conclusion: The magnesium mineral solution with all concentrations has relatively little impact on the water's hydrogen signal, making it impossible to distinguish this impact with the naked eye. Therefore, it is neglected in the clinical study.  The calcium supplement can be employed as a positive contrast agent on T2-weighted images for gastrointestinal imaging